High mobility flexible graphene field-effect transistors and ambipolar radio-frequency circuits. Issue 25 (10th June 2015) - Liang, Yiran; Liang, Xuelei; Zhang, Zhiyong; Li, Wei; Huo, Xiaoye; Peng, Lianmao
Abstract : Field-effect transistors (GFETs) were fabricated on mechanically flexible substrates using chemical vapor deposition grown graphene. Abstract : Field-effect transistors (GFETs) were fabricated on mechanically flexible substrates using chemical vapor deposition grown graphene. High current density (nearly 200 μA μm −1 ) with saturation, almost perfect ambipolar electron–hole behavior, high transconductance (120 μS μm −1 ) and good stability over 381 days were obtained. The average carrier mobility for holes (electrons) is 13 540 cm 2 V −1 s −1 (12 300 cm 2 V −1 s −1 ) with the highest value over 24 000 cm 2 V −1 s −1 (20 000 cm 2 V −1 s −1 ) obtained in flexible GFETs. Ambipolar radio-frequency circuits, frequency doubler, were constructed based on the high performed flexible GFET, which show record high output power spectra purity (∼97%) and high conversion gain of −13.6 dB. Bending measurements show the flexible GFETs are able to work under modest strain. These results show that flexible GFETs are a very promising option for future flexible radio-frequency electronics.